Nitric oxide removal by zinc chloride activated oil palm empty fruit bunch fibre - Cha, Soon Lin; Naimah, Ibrahim; Norhidayah, Ahmad; Muhammad Adli, Hanif; Sureena, Abdullah (Penerbit UTM Press, 2021)
Nitric oxide (NO) emission is known to pose detrimental effects towards the environment and human beings. Low-temperature NO removal by activated carbon from agricultural waste materials is affordable due to the use of low-cost materials as precursor and elimination of the need for flue gas reheating. The use of chemical agents in activated carbon production improves the performance of waste materials in NO removal. The performance of NO removal was investigated via breakthrough experiment using oil palm empty fruit bunch (EFB) activated with zinc chloride (ZnCl2) at different concentrations (0.1, 0.5, and 1.5 M). Activation of EFB with 0.5 M ZnCl2 resulted in the formation of well-defined micropores, but the use of higher concentration of ZnCl2 resulted in widening of developed pores and intense pore blockage which reduce the accessibility of NO molecules to the adsorption sites. An adsorption isotherm study conducted using 0.5 M ZnCl2/EFB sample with varying NO concentration between 300-1000 ppm indicated that the adsorption process was best defined by Langmuir isotherm model. In addition, adsorption kinetic was investigated at different temperatures; i.e. 100, 150, 200, 250 and 300 °C. NO removal was found to follow Avrami kinetic model at T=100 °C, while upon further increase in temperature, the process was better fitted to the pseudo-second order kinetic model. NO adsorption capacity increases significantly beyond 250 °C up to 1000 mg/g. The activation energy of NO adsorption fell into two distinct regions: -4.73 kJ/mol at 100-200 °C and 84.04 kJ/mol at 200-300 °C. At lower temperature, the adsorption process was exothermic and followed physisorption path, while the increase in reaction temperature led to slower rate of reaction. It was concluded that the removal of NO using EFB modified with ZnCl2 at optimized condition could be a promising alternatives for treating NO-containing flue gas.